Identifikasi Molekuler Bakteri Simbion Spons Spongia sp. Penghasil Antibakteri - Latifah Ningrum Abdillah; Sri Muri Dasa Wardhani (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2026)
This study aims to identify antibacterial-producing symbiotic bacteria in sponges using a molecular approach based on 16S ribosomal RNA (16S rRNA) genes as an initial step towards the sustainable use of marine biological resources. A total of six symbiotic bacterial isolates were successfully isolated from Spongia sp. sponges and exhibited differences in colony morphology characteristics. All isolates were tested for antibacterial activity against Escherichia coli and Bacillus subtilis. The test results showed that all isolates had the ability to inhibit the growth of test bacteria with inhibition zone diameters ranging from 5.0–8.5 mm against E. coli and 6.0–9.0 mm against B. subtilis. Among all isolates, Sp2 exhibited the highest antibacterial activity and was broad-spectrum, with stronger inhibitory power against Gram-positive bacteria. Isolate Sp2 was further molecularly identified using the 16S rRNA gene. Amplification results showed a DNA fragment of approximately 520 base pairs. Phylogenetic analysis based on the 16S rRNA gene sequence placed isolate Sp2 within the Bacillus genus, with the closest affiliation to Bacillus subtilis and supported by high bootstrap values, indicating a strong genetic relationship. Overall, the results of this study indicate that isolate Sp2 is the most promising symbiotic bacterium of the sponge Spongia sp. as a producer of antibacterial compounds against E. coli and B. subtilis. This isolate has the potential to be further developed as a source of antibacterial bioactive compounds, thus requiring further research to identify and characterize the active compounds it produces.